2016
DOI: 10.1890/15-1964.1
|View full text |Cite
|
Sign up to set email alerts
|

Predation risk increases immune response in a larval dragonfly (Leucorrhinia intacta)

Abstract: Predators often negatively affect prey performance through indirect, non-consumptive effects. We investigated the potential relationship between predator-induced stress and prey immune response. To test this, we administered a synthetic immune challenge into dragonfly larvae (Leucorrhinia intacta) and assessed a key immune response (level of encapsulation) in the presence and absence of a caged predator (Anax junius) at two temperatures (22 degrees C and 26 degrees C). We hypothesized that immune response woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 41 publications
2
29
0
Order By: Relevance
“…S2). These results, in conjunction with previous work (Duong and McCauley, ; Van Allen et al ., ), suggest that, similar to predators, potentially cannibalistic conspecifics may have indirect beneficial effects on their potential prey by decreasing their risk of future pathogen infections (Moret and Siva‐Jothy, ) via immune enhancement. Alternatively, individuals exposed to potential cannibals that induce an immune priming response could be disadvantaged if the priming is costly and reduces the resources available for other life history challenges (e.g.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…S2). These results, in conjunction with previous work (Duong and McCauley, ; Van Allen et al ., ), suggest that, similar to predators, potentially cannibalistic conspecifics may have indirect beneficial effects on their potential prey by decreasing their risk of future pathogen infections (Moret and Siva‐Jothy, ) via immune enhancement. Alternatively, individuals exposed to potential cannibals that induce an immune priming response could be disadvantaged if the priming is costly and reduces the resources available for other life history challenges (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…Although it is not possible to make direct comparisons across experiments, qualitatively, the effect of conspecifics appears to be similar to the effect of top predators on the melanisation response; Duong and McCauley (2016) showed that the threat of predation positively correlated with an increased immune response in L. intacta larvae (comparing our Figs 1 and 2 with the results from Duong and McCauley (2016). Previous studies have shown that tadpole prey show stronger behavioural and physiological plasticity in response to kairomones and alarm cues associated with a dragonfly predator consuming conspecifics compared with experimentally crushed conspecifics (Schoeppner and Relyea, 2005) or the presence of a predator (Schoeppner and Relyea, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…haemocyte number, Joop and Rolff, 2004;phenoloxidase activity, Slos et al, 2009; melanization of implants, Duong and McCauley, 2016), with one study (Op de Beeck et al, 2016) finding a negative effect of predator cues on phenoloxidase activity in mosquito larvae (when measured on the whole animal, as opposed to haemolymph levels). The effect on inducible mechanisms (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Such a perspective may help make sense of the mix of increased and decreased immune functions found in larval insects exposed to chronic predator stress (e.g. Joop and Rolff, 2004;Slos et al, 2009;Duong and McCauley, 2016;Op de Beeck et al, 2016).…”
Section: Introductionmentioning
confidence: 99%